Transcriptomic approach for assessment of the impact on microalga and macrophyte of in-situ exposure in river sites contaminated by chlor-alkali plant effluents. (15th September 2017) - Dranguet, Perrine; Cosio, Claudia; Le Faucheur, Séverine; Beauvais-Flück, Rebecca; Freiburghaus, Aline; Worms, Isabelle A.M.; Petit, Brice; Civic, Natacha; Docquier, Mylène; Slaveykova, Vera I.
Abstract: Water quality degradation is a worldwide problem, but risk evaluation of chronic pollution in-situ is still a challenge. The present study aimed to evaluate the potential of transcriptomic analyses in representative aquatic primary producers to assess the impact of environmental pollution in-situ : the microalga Chlamydomonas reinhardtii and the macrophyte Elodea nuttallii were exposed 2 h in the Babeni Reservoir of the Olt River impacted by chlor-alkali plant effluent release resulting in increased concentrations of Hg and NaCl in receiving water. The response at the transcriptomic level was strong, resulting in up to 5485, and 8700 dysregulated genes (DG) for the microalga and for the macrophyte exposed in the most contaminated site, respectively. Transcriptomic response was congruent with the concentrations of Hg and NaCl in the water of the impacted reservoir. Genes involved in development, energy metabolism, lipid metabolism, nutrition, and RedOx homeostasis were dysregulated during in-situ exposure of both organisms. In addition, genes involved in the cell motility of C. reinhardtii and development of the cell wall of E. nuttallii were affected. DG were in line with adverse outcome pathways and transcriptomic studies reported after exposure to high concentrations of Hg and NaCl under controlled conditions in the laboratory. Transcriptomic response provided a sensitive measurement of the exposure as well as hints on the tolerance mechanisms of environmental pollution, and is thus promising as an early-warning tool to assess water quality degradation. Graphical abstract: Highlights: A green microalga and a macrophyte were exposed 2 h in-situ in the Olt River. Transcriptomic response was strong and congruent with gradients of Hg and NaCl. It also was consistent with expected adverse outcome pathways for Hg and NaCl. Transcriptomic response was more sensitive than Hg bioaccumulation. Transcriptomic is a promising early-warning tool of water quality degradation.